Trauma-focused treatment outcome for complex PTSD patients: results of an intensive treatment programme. Issue 1 (31st December 2020) - Voorendonk, Eline M.; De Jongh, Ad; Rozendaal, Linda; Van Minnen, Agnes
ABSTRACT: Background: Complex PTSD (CPTSD) has been incorporated in the 11th edition of the International Classification of Diseases (ICD-11) as a mental health condition distinct from PTSD. Objective: The objective of the current study is to determine whether individuals classified as having CPTSD can benefit from an intensive trauma-focused treatment, resulting in decreased PTSD and CPTSD symptoms, and loss of diagnoses. Method: Patients diagnosed with PTSD ( N = 308) took part in an intensive 8-day treatment programme combining prolonged exposure, EMDR therapy, psycho-education, and physical activity. The treatment was not phase-based in that it did not contain a stabilization phase or skill training prior to therapy. CPTSD diagnosis was assessed by means of the International Trauma Questionnaire (ITQ) and PTSD diagnosis was assessed with both the ITQ and CAPS-5. Treatment response was measured with the CAPS-5, PCL-5, and ITQ. Results: Symptoms of both PTSD and CPTSD significantly decreased from pre- to post-treatment resulting in a significant loss of CAPS-5 based PTSD (74.0%) and ITQ-based PTSD and CPTSD diagnoses (85.0% and 87.7%, respectively). No adverse events occurred in terms of suicides, suicide attempts, or hospital admissions. Conclusions: The results are supportive of the notion that the majority of patients classified as having CPTSD strongly benefit from an intensive trauma-focused treatment for their PTSD.